Evaluation of Supplemental Energy Source for Grazing Stocker Cattle - L. W. Lomas; J. K. Farney; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 108 steers grazing smooth bromegrass pastures were used to evaluate the effects of supplemental energy source on available forage, grazing gains, subsequent finishing gains, and carcass characteristics in 2014, 2015, and 2016. Supplementation treatments evaluated were: no supplement, a supplement with starch as the primary source of energy, and a supplement with fat as the primary source of energy. Supplements were formulated to provide the same quantity of protein and energy per head daily. Supplementation with the starch-based or fat-based supplement during the grazing phase resulted in higher (P<0.05) grazing gains than feeding no supplement during all three years. In 2014 and 2016, grazing gains of steers supplemented with the starch-based or fat-based supplement were similar (P>0.05). In 2015, steers supplemented with the fat-based supplement had greater (P<0.05) grazing gains than those that received the starch-based supplement. In 2014, supplementation during the grazing phase had no effect (P>0.05) on finishing gain, feed intake, and feed:gain. Steers supplemented with the starch-based supplement had greater (P<0.05) final finishing liveweight, and greater (P<0.05) hot carcass weight than those that received no supplement. In 2015, steers fed the fat-based supplement had higher (P<0.05) final finishing liveweight, greater (P<0.05) hot carcass weight, and lower (P<0.05) finishing gain than those supplemented with the starch-based supplement or fed no supplement.
Keywords: supplementation; energy; grazing; stocker cattle; finishing; marbling